Enhancement of mechanical properties of bagasse-fiber plastic composite via nano silica and maleic anhydride grafted high density polyethylene (MAPE) addition - Zaini, Mohd Nazmir (2018)
Wood plastic composite using bagasse fibre and recycled high density polyethylene (rHDPE) were developed in this study. Modification of nano- silica and maleated polyethylene (MAPE) were mixed to improve interfacial bonding. The objective of this study was to determine the effect of percentage of fibre loading and modification using nano-silica filler on mechanical properties of WPC produced from bagasse fibre and recycled HDPE. The rHDPE was melted at 130oC and directly blended with bagasse fibre, nano-silica and MAPE according to various mixture percentages. The compounds materials were compressed into a mould 150mm x 150mm x 30mm. The boards were cut into test samples for mechanical assessments which is tensile testing and flexural testing in accordance with ASTM standard. It was found that fibre loading has more apparent influence on the strength properties of bagasse composites. The tensile MOR, MOE and flexural MOR decreased while flexural MOE increased with the increasing of fibre loading. The study also concluded that addition of nano-silica has significantly improved the MOR and MOE of the composite material.